Determination of Disiplinary Penalties for Civil Servants for Divorce Permin Violations - Gayatri, Paramita Dewi; Widarto, Joko; Juanda, Juanda; Subiyanto, Achmad Edi (Journal of Law, Politic and Humanities, 2025)
This research is a normative research that focuses not only on examining secondary materials but also primary materials. The approach method used is laws and regulations and cases. The purpose of this study is to determine the determination of the imposition of types of disciplinary penalties, especially violations of divorce permits within the Ministry of Finance. Based on Article 41 of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline, if a violation of marriage and divorce permits is subject to one type of severe disciplinary punishment. The results showed that the Ministry of Finance in determining the type of disciplinary punishment is based on weighting first before getting the main value as outlined in Minister of Finance Regulation Number 123 of 2023 concerning Procedures for Examining Disciplinary Violations and Imposition of Disciplinary Penalties within the Ministry of Finance. In the weighting, it has also considered the elements of lightening and aggravating as stated in the Regulation of the State Personnel Agency Number 6 of 2022 concerning Implementation Regulations of Government Regulation Number 94 of 2021 concerning Discipline of Civil Servants